Crilin: A CRystal calorImeter with Longitudinal InformatioN for a future Muon Collider. (26th September 2022) - Ceravolo, S.; Colao, F.; Curatolo, C.; Di Meco, E.; Diociaiuti, E.; Lucchesi, D.; Paesani, D.; Pastrone, N.; Saputi, A.; Sarra, I.; Sestini, L.; Tagnani, D.
Abstract: The measurement of physics processes at new energy frontier experiments requires excellent spatial, time, and energy resolutions to resolve the structure of collimated high-energy jets. In a future Muon Collider, the beam-induced backgrounds (BIB) represent the main challenge in the design of the detectors and of the event reconstruction algorithms. The technology and the design of the calorimeters should be chosen to reduce the effect of the BIB, while keeping good physics performance. Several requirements can be inferred: i) high granularity to reduce the overlap of BIB particles in the same calorimeter cell; ii) excellent timing (of the order of 100 ps) to reduce the out-of-time component of the BIB; iii) longitudinal segmentation to distinguish the signal showers from the fake showers produced by the BIB; iv) good energy resolution (less than 10%/ √E ) to obtain good physics performance, as has been already demonstrated for conceptual particle flow calorimeters. Our proposal consists of a semi-homogeneous electromagnetic calorimeter based on lead fluoride crystals (PbF2 ) read out by surface-mount UV-extended Silicon Photomultipliers (SiPMs): the Crilin calorimeter. In this paper, the performance of the Crilin calorimeter in the Muon Collider framework for hadron jets reconstruction has been analyzed. We report the characterisation of individual components together with the development of a small-scale prototype, consisting of 2 layers of 3 × 3 crystals each.